Hematidrosis in young lass: an omen of stress - Kamaruzaman, Nor Azam; Abd Rahman, Mohd Aizuddin; Musa, Noraini; Osman, Iskandar Firzada (Malaysian Medical Association, 2022)
Hematidrosis, also known as hematohidrosis, is an unusual disorder in which healthy skin secretes blood. Scarce case reports mainly occurred in adolescent Asian girls. It is common to misdiagnose hematidrosis as a consequence of self-harm because it is often triggered by severe stress or psychiatric disorders. Early diagnosis will enable rapid treatment and intervention of the underlying diseases and stress, making it essential to understand this disease and its clinical features. We describe a case report of a 16-year-old Malay girl who presented to the clinic with a one-month history of episodic sweating blood from her forehead and occasionally bloody tears. Specific investigation to establish the diagnosis is still a dilemma, but a more significant challenge in primary care is identifying and managing a teenage patient's stressor.